2021
DOI: 10.1109/access.2021.3091537
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Analysis and Visualization of Arabic Tweets During the COVID-19 Pandemic

Abstract: Twitter data have been used widely in times of pandemics and crises. Currently, the world is suffering from the outbreak of new coronavirus disease 2019 , in which the COVID-19 virus has infected more than one hundred and twenty million people worldwide with more than two million deaths. Consequently, people tend to share COVID-19-related content on social media extensively. As a new pandemic, only a small number of studies have been conducted to analyze COVID-19-related tweets, and even fewer were meant for A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Closeness centrality (CC) calculates the average distance between a node and all other nodes on the network. This measure describes the proximity of this node to other nodes [24] as in Eq. ( 2).…”
Section: B Network Analysis Research Using Social Network Analysismentioning
confidence: 99%
“…Closeness centrality (CC) calculates the average distance between a node and all other nodes on the network. This measure describes the proximity of this node to other nodes [24] as in Eq. ( 2).…”
Section: B Network Analysis Research Using Social Network Analysismentioning
confidence: 99%
“…Al-Shargabi et al [4] proposed a research study to explore the spread and the effects of the COVID-19 pandemic by analyzing the tweets of Saudi Arabia Twitter users. They collected 8905 Arabic tweets to visualize the social network for COVID-19 pandemic tweets of Saudi users.…”
Section: Related Workmentioning
confidence: 99%
“…Due to the great importance of the social networks, so it can be considered one of the main directions for many researches. Al-Shargabi et al [4] proposed a research study to explore the effects of the COVID-19 global epidemic by analyzing the tweets of Saudi Arabia Twitter users. They collected 8905 Arabic tweets to visualize the social network graph for the COVID-19 tweets of the people who live at Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…The number of social media users has been growing rapidly in the past decade. People discuss and share information and opinions on social media platforms [4]. It has been reported that two-thirds of American adults use social media to post their status, opinions, and other information on a regular basis.…”
Section: Introductionmentioning
confidence: 99%